DAMPAK SOSIO-EKONOMI DALAM KEBERADAAN KAMPUNG KULINER DI TALANG BANDUNG KABUPATEN OGAN KOMERING ULU - Kurniawan, Yoland; Pusvita, Ema; Ogari, Putri Ayu (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study has the aim of knowing whether the existence of a culinary village in Talang Bandung has an impact on the social and economy of the community and whether before and after the existence of a culinary village in Talang Bandung has had an impact on the social and economy of the community. The method used is the case study method. Data collection uses a questionnaire that will be filled out by Kampung Kuliner UKM traders with analytical tools namely descriptive analysis and T-test. The results of this study are that there is a social impact which is able to change perspectives in looking for work, entrepreneurial mindset and high social interaction. Economically able to increase income because people have additional businesses. The difference in income before and after joining the culinary village can be seen in the results of the T-Paired Samples Correlations test of 0.000 <0.05.